Implementasi Organizational Social Responsibility dalam Membangun Citra BPJS Kesehatan Bengkulu - Putra, Meidy Triansyah; Afifi, Subhan (Jurnal Ilmiah Multimedia dan Komunikasi, 2022)
Implementation of the Organizational Social Responsibility (OSR) Program positively impacts the community and supports an increase in the organization's image or reputation. This study examines the implementation of the OSR of BPJS Kesehatan Bengkulu, including inhibiting and supporting factors in its implementation. BPJS Kesehatan is Healthcare and Social Security Agency in Indonesia. This qualitative descriptive study uses a case study method that collects data through in-depth interviews and observation. The research results were analyzed by thematic analysis to produce specific patterns and themes in implementing the OSR program. The research finding shows that the OSR program implementation started with planning, performance, and evaluation. The OSR programs are accepted well by the community, which will contribute to improving the image of Â BPJS Kesehatan Bengkulu.